2008
DOI: 10.1111/j.1460-9568.2008.06039.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the primary motor and sensory cortex in precision grasping: a transcranial magnetic stimulation study

Abstract: Human precision grip requires precise scaling of the grip force to match the weight and frictional conditions of the object. The ability to produce an accurately scaled grip force prior to lifting an object is thought to be the result of an internal feedforward model. However, relatively little is known about the roles of various brain regions in the control of such precision grip-lift synergies. Here we investigate the role of the primary motor (M1) and sensory (S1) cortices during a grip-lift task using inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…First, although SI and M1 are anatomically close and highly interconnected, there is physiological and behavioral evidence that the aftereffect of SI and M1 cTBS can dissociate (Ishikawa et al, 2007, Mochizuki et al, 2007, Ragert et al, 2008, Schabrun et al, 2008). Second, although neural activity in M1 may be modulated by action observation (Nishitani and Hari, 2000, Fadiga et al, 2005, Caetano et al, 2007; Schütz–Bosbach et al, 2009; Gazzola and Keysers, 2009; Vigneswaran et al, 2013), it is debated whether such activity might play a major role in action perception (Lepage et al, 2008, Pineda, 2008, Bonini, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…First, although SI and M1 are anatomically close and highly interconnected, there is physiological and behavioral evidence that the aftereffect of SI and M1 cTBS can dissociate (Ishikawa et al, 2007, Mochizuki et al, 2007, Ragert et al, 2008, Schabrun et al, 2008). Second, although neural activity in M1 may be modulated by action observation (Nishitani and Hari, 2000, Fadiga et al, 2005, Caetano et al, 2007; Schütz–Bosbach et al, 2009; Gazzola and Keysers, 2009; Vigneswaran et al, 2013), it is debated whether such activity might play a major role in action perception (Lepage et al, 2008, Pineda, 2008, Bonini, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, continuous TBS (cTBS) has been shown to have a similar but longer effect to that of slow rTMS (that is, inhibitory) when applied to the motor cortexF20 s of stimulation may result in a lasting effect of up to 20 min, and 40 s of stimulation up to 60 min. This long-lasting inhibitory effect of cTBS has been replicated by several groups over the primary motor area (Huang et al, 2007a), the premotor area (Koch et al, 2007;Mochizuki et al, 2005), the primary sensory area (Schabrun et al, 2008), the primary visual areas (Franca et al, 2006), the frontal eye field (Hubl et al, 2008), and the DLPFC (Vallesi et al, 2007). Furthermore, cTBS inhibits the BOLD fMRI signal for over 30 min when applied to the frontal eye field (Hubl et al, 2008).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 90%
“…It seems obvious that, during the preload phase, the central nervous system needs information indicating a reliable contact before releasing the muscle commands leading to the load phase. Previous studies have shown that the duration of the preload phase is increased in very young children [31], in older adults [32], in children and adults with hemiplegia [28,33] and in healthy adults following repetitive transcranial magnetic stimulation of the primary somatosensory cortex [34]. In most of these studies, it seems likely that the increased duration of the preload phase results from an altered cortical processing of the sensory signals generated by the contact of the fingers with the object and/or integration of that information into the movement plan.…”
Section: Discussionmentioning
confidence: 99%